Rice (Oryza sativa L.) Growth and Production in Main Square System Treatment with Liquid Organic Fertilizer of Gold Snails (Pomacea caniculata L.) and Citronella Oil (Cymbopogon nardus (L.) Rendle) - Sunadi, Sunadi; Utama, M Zulman Harja; Auldina, Melia (Journal of Applied Agricultural Science and Technology, 2023)
The use of artificial chemicals as fertilizers and pesticides can endanger the health of the environment and consumers, so the potential utilization of natural materials as fertilizers and pesticides needs to be increased from local sources such as golden snails and citronella. The experiment aims to get the best interaction between golden snail Liquid Organic Fertilizer (LOF) and citronella oil for rice growth and production. The experiment was carried out in the paddy fields of Jorong Paraman Ampalu, Gunung Tuleh District, West Pasaman Regency from September 2020 to January 2021 using an RBD of 2 factors with 3 replications. The first factor was the golden snail LOF concentration, namely: 0, 100, 200, and 300 ml/L. The second factor was the citronella oil concentration, namely: 0, 10, 20, and 30 ml/L. Data were analyzed with ANOVA and DNMRT at 5% and 1%. The experimental results showed that the interaction between golden snail LOF and citronella oil concentration accelerated flowering, increased panicle length, grain weight, and dry grain production per hectare, while the golden snail LOF concentration factor increased plant height, maximum number of tillers and productive tillers, panicle length, number of grains per panicle, and 1000 grain weight. The highest grain production was obtained at concentrations of golden snails LOF of 200 ml/L and citronella oils 20 ml/L, namely 9.18 t/ha. The frequency of attacks by ground beetles and golden snails decreased at a concentration of 30 ml/L citronella oil, while stink bug infestation frequency was reduced at a concentration of 10 ml/L.